When Empathic Concern and Perspective Taking Matter for Ethical Judgment: The Role of Time Hurriedness - Cojuharenco, Irina (Journal of business ethics, 2015)
Based on a dual process view of ethical judgment, we examine the role of empathic concern and perspective taking on the acceptability of lying to protect the company. We hypothesize that these traits will matter to a different extent under conditions of high and low perceived time hurriedness. Our research hypotheses are tested in a survey of 134 US workers. Results show that empathic concern reduces the acceptability of lying to protect the company for individuals who tend to do things quickly and feel in a hurry at work. On the other hand, perspective taking reduces the acceptability of lying for individuals who experience low levels of time hurriedness. Theoretical and practical implications of the findings are discussed.